2022
DOI: 10.3390/ijms231911664
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and DNA Damage Markers in Colorectal Cancer

Abstract: Oxidative stress (OS) and inflammation are known to play an important role in chronic diseases, including cancer, and specifically colorectal cancer (CRC). The main objective of this study was to explore the diagnostic potential of OS markers in patients with CRC, which may translate into an early diagnosis of the disease. To do this, we compared results with those in a group of healthy controls and assessed whether there were significant differences. In addition, we explored possible correlations with the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…We showed previously that EspF increases the production of ROS and induces the generation of γ-H2AX ( 5 , 41 ), suggesting that signs of oxidative DNA lesions exist during EHEC infection. To explore this hypothesis, we determined the level of 8-oxoG, the most abundant DNA lesion after exposure to oxidative stress, which serves as an oxidative stress biomarker for CRC ( 4 ). Caco-2 cells were incubated with the indicated strains for 6 and 9 h, and a time-dependent increase in ROS levels dependent on EspF was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed previously that EspF increases the production of ROS and induces the generation of γ-H2AX ( 5 , 41 ), suggesting that signs of oxidative DNA lesions exist during EHEC infection. To explore this hypothesis, we determined the level of 8-oxoG, the most abundant DNA lesion after exposure to oxidative stress, which serves as an oxidative stress biomarker for CRC ( 4 ). Caco-2 cells were incubated with the indicated strains for 6 and 9 h, and a time-dependent increase in ROS levels dependent on EspF was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress and subsequent DNA lesions are considered as a starting point in the development of colitis-associated cancer ( 3 ). 8-Oxoguanine (8-oxoG) and phosphorylated histone H2A variant H2AX are commonly used as biomarkers for oxidative DNA damage and double-strand breaks (DSBs) in colorectal cancer (CRC) ( 4 ). Although the tumorigenic potential of EHEC has been previously discussed ( 5 7 ), there is limited evidence of the mechanisms underlying the formation of oxidative DNA lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that an elevated OBS reduces the risk of secondary metastasis and abdominal pain caused by proximal colon cancer, yet it elevates the risk of secondary metastasis and abdominal pain induced by distal colon cancer. This may be due to the fact that differences in genetic and molecular characteristics of proximal colon cancer result in antioxidants having a more positive effect, such as reducing DNA damage caused by oxidative stress, thereby lowering the risk of metastasis and symptoms induced by the tumor ( 35 ). Some antioxidants may promote the proliferation and metastasis of existing tumor cells at high doses, especially when the tumor cells have adapted to a high oxidative stress environment ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro assays showed that overexpression of ACOX2 leads to decreased cellular lipid content and elevated cellular ROS content in PCa cell lines with upregulated CAT expression. Overcoming the degradation ability of peroxidases such as CAT, the excessive generation of ROS results in oxidative stress 32 and cell cycle arrest 33 . It has been reported that ROS leads to G2/M arrest in cervical carcinoma 34 and colorectal cancer cells 35 .…”
Section: Discussionmentioning
confidence: 99%